Relevancy of Corporate Financial Policies and the Profit Maximization View of Islamic Banks - Taskinsoy, John (Journal of Social and Development Sciences, 2012)
This paper examines relevancy of corporate financial policies and documents similarities and/or differences of how profit maximization goal is viewed by Islamic banking institutions (IBIs). Management of the firm is ultimately responsible for maximizing profits and increasing shareholder value, however this challenging task may get plagued by agency problems as well corporate financial policy conflicts. Agency problem is real and it is assumed to occur in most companies worldwide. However, the theory’s controversial nature and its narrow focus have not really convinced many scholars whether agency theory in fact provides any broad benefits to firm’s stakeholders or not. Scholars seem to be divided into two camps on agency theory. Some authors think that agency theory pays too much attention to short-term goal of share price valuation and it hardly provides any real answers to firm’s real problems. On the other hand, some proponents of this theory believe agency theory’s useful impact on capital markets.